2014
DOI: 10.4321/s1886-36552014000200005
|View full text |Cite
|
Sign up to set email alerts
|

PERSYVE: design and validation of a questionnaire about adverse effects of antihypertensive drugs

Abstract: ObjectiveThe aim of this study was to design and validate a questionnaire to measure perceived symptoms associated with antihypertensive drugs (PERSYVE).MethodsThe PERSYVE development and validation included four stages: 1) item development (bibliographic review and questionnaire elaboration); 2) face and content validation; 3) field testing (pre-test); and 4) test-retest validation, assessment of internal consistency (Cronbach’s alpha) and reproducibility over time (intraclass correlation coefficient and Cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Previous research has shown that questionnaires can be useful instruments in obtaining information from patients about adverse events and about, for instance, the time course, severity, and outcome of the adverse events [15,16]. Even though researchers have developed several questionnaires in the past [15][16][17], they were developed for other types of drugs and are not suitable for radiopharmaceuticals because of aspects that are unique to the use of these products in nuclear medicine departments. Examples are the specific preparation of the patient before the nuclear medicine examination or additional steps during the procedure such as physical exercise or the concomitant administration of interventional agents, like agents that induce stress in the case of the assessment of myocardial perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that questionnaires can be useful instruments in obtaining information from patients about adverse events and about, for instance, the time course, severity, and outcome of the adverse events [15,16]. Even though researchers have developed several questionnaires in the past [15][16][17], they were developed for other types of drugs and are not suitable for radiopharmaceuticals because of aspects that are unique to the use of these products in nuclear medicine departments. Examples are the specific preparation of the patient before the nuclear medicine examination or additional steps during the procedure such as physical exercise or the concomitant administration of interventional agents, like agents that induce stress in the case of the assessment of myocardial perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…It varies from 0 to 1, and shows the extent to which all the ingredients of the test measure the same concept. For an instrument with variables with a nominal/ordinal outcomes (such as a 1-7 Likert scale), it is acceptable to obtain Cronbach's alpha values above 0.7 (21,22). Secondly, the questionnaire was divided randomly into two parts with the same number of questions, and Cronbach's alpha for each part was Acta facultatis medicae Naissensis 2016;33(4):247-258 251 Unauthenticated Download Date | 5/13/18 3:52 AM calculated.…”
Section: Reliability Testingmentioning
confidence: 99%
“…The review ended with 15 questions which were comprised by the final instrument. Pilot testing of the questionnaire was performed with 7 pharmacists and 30 patients on statin therapy, by the same researcher, to evaluate the clarity and comprehension (22). The results of the pilot testing were not taken into account when processing data for the validation of the questionnaire.…”
Section: Construction Of the Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the undesirable effects of antihypertensive drugs may also interfere with the quality of life of patients and lead to a limited therapeutic adherence. (9) In addition, effects of the disease itself on the quality of life can generate emotional impacts on people's lives, and make them give up the medication, see no reasons for medication intake, do not realize advances in treatment, think a lot about the limitations or do not realize improvement in their behavior. Therefore, it is easy to notice the complex interaction between quality of life in hypertensive patients and medication adherence, which should be better understood by health professionals.…”
Section: Introductionmentioning
confidence: 99%